Health Financing in Indonesia : A Reform Road Map - Rokx, Claudia; Schieber, George; Tandon, Ajay; Harimurti, Pandu; Somanathan, Aparnaa (World Bank, 2012)
Indonesia is at a critical stage in the development and modernization of its health system. The government of Indonesia has made major improvements over the past four decades, but struggles to maintain and continue to improve important health outcomes for the poor and achieve the Millennium Development Goals. Nevertheless, some key health indicators show significant progress. Infant and child (under five) mortality rates have fallen by half since the early 1990s, although the speed of the decline appears to have slowed since 2002. Maternal mortality rates show a declining trend, but remain among the highest in East Asia. Indonesia's population program is one of the worlds most successful: fertility rates have declined impressively since the 1970s and continue to fall. Previously declining malnutrition rates among young children have, however, stagnated. The slowing down of progress may be explained by a poorly functioning health system as well as by new and ongoing challenges posed by demographic, epidemiological, and nutrition transitions, which require new policy directions, a reconfigured and better performing health system, and long-term sustainable financing.